2023
DOI: 10.1007/s10840-023-01474-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved 1-year outcomes after active cooling during left atrial radiofrequency ablation

Abstract: Background Active esophageal cooling during pulmonary vein isolation (PVI) with radiofrequency (RF) ablation for the treatment of atrial fibrillation (AF) is increasingly being utilized to reduce esophageal injury and atrioesophageal fistula formation. Randomized controlled data also show trends towards increased freedom from AF when using active cooling. This study aimed to compare 1-year arrhythmia recurrence rates between patients treated with luminal esophageal temperature (LET) monitoring v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Insulating effects from the pericardial fat, fibrous pericardium, and serous layers minimize cooling in the atrial myocardium so that effective lesions can still be placed,[33] with long-term follow up data confirming no decrease in freedom from atrial arrhythmias at one year with active esophageal cooling compared with LET monitoring. [32] A larger volume of retrospective data further suggests improvement in freedom from arrhythmias with cooling,[42] which may be due to differences in lesion placement sequence with the catheter, enabled by having cooling in place. [43, 44]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulating effects from the pericardial fat, fibrous pericardium, and serous layers minimize cooling in the atrial myocardium so that effective lesions can still be placed,[33] with long-term follow up data confirming no decrease in freedom from atrial arrhythmias at one year with active esophageal cooling compared with LET monitoring. [32] A larger volume of retrospective data further suggests improvement in freedom from arrhythmias with cooling,[42] which may be due to differences in lesion placement sequence with the catheter, enabled by having cooling in place. [43, 44]…”
Section: Discussionmentioning
confidence: 99%
“…Insulating effects from the pericardial fat, fibrous pericardium, and serous layers minimize cooling in the atrial myocardium so that effective lesions can still be placed, [33] with long-term follow up data confirming no decrease in freedom from atrial arrhythmias at one year with active esophageal cooling compared with LET monitoring. [32] A larger volume of retrospective data further suggests improvement in freedom from arrhythmias with cooling, [42] which may be due to differences in lesion placement sequence with the catheter, enabled by having cooling in place. [43,44] To date, no AEF has yet been identified in a patient treated with active esophageal cooling using a dedicated esophageal cooling device, and only a single pericardio-esophageal fistula has been reported despite over 22,000 RF catheter ablations now completed using this cooling device.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is also seen in RF ablation, both in mathematical models 10 and in clinical data, where long-term follow-up has shown improvement in freedom from arrhythmia (postablation period in which the patient does not present with evidence of arrhythmia) with the use of PEC. 37,38 The presence of interspersed tissues between the atrial wall and the esophagus (such as the visceral and parietal layers of the fibrous pericardium, the pericardial space and serous fluid, and the pericardial fat), all of which have low or no tissue perfusion, likely contributes to this phenomenon by providing an effective insulating layer between the cooled esophagus and the myocardial tissue (atrial wall) being heated intentionally to induce targeted lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with LET monitoring were performed by 3 of the 4 operators using proactive esophageal cooling, but this study otherwise followed the same operators with consistent procedural approaches, operating within the same hospital system, and serving the same patient demographic over the time period. Long-term follow-up comparison of procedural outcome is not available for the cases reviewed in this analysis; however, abundant data, including prospective randomized controlled trial data 8 , as well as larger retrospective data from this same site 9 , support the improved efficacy from proactive esophageal cooling, and ongoing randomized trials (NCT04577859) will continue to quantify this effect size.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term follow-up from the 120 patient IMPACT randomized controlled trial found a 3% (p=ns) absolute improvement, and a 513 patient review found a 14% absolute improvement (p=0.03) in freedom from arrhythmia at one year. 8,9 A potential mechanism for an improvement in long-term freedom from AF with proactive esophageal cooling is via improvement in lesion contiguity, or lesion sequentiality. 2,3 Lesion contiguity has been characterized using the Continuity Index, which is a quantification determined by the number of non-contiguous, or non-adjacent, lesions placed.…”
Section: Introductionmentioning
confidence: 99%